Transdentinal diffusion and cytotoxicity of self-etching adhesive systems - Moreira Lanza, Celia Regina; Souza Costa, Carlos Alberto de [UNESP]; Furlan, Maysa [UNESP]; Alecio, Alberto [UNESP]; Hebling, Josimeri [UNESP] (Springer, 2009)
To evaluated the transdentinal diffusion and subsequent cytotoxicity of self-etching adhesives on odontoblast-like cells.Sixty dentin disks (0.4-mm thick) were produced from human molars and divided into six groups (n = 10). The dentin disks were placed in in vitro pulp chambers where MDPC-23 cells were planted on 0.28 cm(2) of exposed dentin on the pulpal side. The adhesives Clearfil SE Bond (CSE), Clearfil Protect Bond (CPB), Adper Prompt (PR), and Xeno III (XE) were applied on the occlusal side. Single Bond (SB) was used as positive and phosphate buffer solution (PBS) as negative control. The cytotoxicity was measured by MTT assay and cell characteristics were assessed by SEM. The transdentinal diffusion was qualified by GC/MS.Kruskal-Wallis and Mann-Whitney tests demonstrated a significant difference among the adhesives and PBS. Cellular viability reduction promoted by the self-etching systems was lower than that of SB (53.1%), except for CSE. Cell metabolism was reduced in 47.8%, 42.1%, 28.0%, and 46.5% for CSE, CPB, PR, and XE, respectively. HEMA was identified as the main diffused component.Components from all investigated self-etching adhesive systems were able to diffuse through the dentin resulting in significant reduction of the cellular metabolism.
Keywords: Cell culture; Cytotoxicity; Dentin; Dentin-bonding agents; Odontoblasts